ANALYSIS OF BANKRUPTCY PREDICTION USING AL-MAN Z-SCORE AND SPRINGATE METHOD IN PT GARUDA INDONESIA TBK PERIOD 2015- 2019 - Sihabudin; Isyanto, Puji; Haizam Mohd Saudi, Mohd (International Journal of Psychosocial Rehabilitation, 2020)
This study analyzes the condition of airlines in Indonesia. There are 15 airlines in Indonesia. However, only 3 companies have been listed on the Indonesia Stock Exchange. This study chose PT Garuda Indonesia Tbk to be the source of research using financial statement data from 2015 to 2019. There are several methods commonly used to analyze bankruptcy, the Altman Z-Score and Springate methods used in this study. The Altman Z-Score method states that PT Garuda Indonesia Tbk is in a gray area condition with an average Z value of 1,686 while the Springate method states that PT Garuda Indonesia is not bankrupt (healthy) with an average value of S 1,271.